Advanced ultrasonic NDE of composite airframe components: physics, modelling and technology - Mienczakowski, Martin (2010)
In recent years the use of composites in engineering has greatly increased due to the advantages which may be obtained. These are weight savings, increased strength, the ability to construct complex geometries and the use of mixed materials. Of particular interest in this work are carbon fibre reinforced plastics (CFRP) which are increasingly used in the aerospace industry. Historically, NDE methods for CFRPs have concentrated on through thickness measurements of ultrasonic attenuation or velocity to determine the presence of defects. Whilst this method is relatively fast and easy to employ there are significant disadvantages in terms of defect characterisation and the location of defects in three dimensions. The advent of full waveform capture and increased computing power allowing processing of large volumes of data, has made 3-D characterisation possible for the first time.